Strategies to Improve Youth Character in Maintaining Relationship between Chinese-Indonesian Culture - Piliang, Faisal (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2019)
Strengthening character is one of the priority programs of President Joko Widodo and Vice President Jusuf Kalla. In his mind, it was stated that the government would revolutionize the nation's character. This study uses a decision support system that is used to select strategies that can be used to improve the character of young people in maintaining the relationship between Chinese-Indonesian culture. The research approach uses hierarchical analytical processes and multi-criteria decision making using expert choice applications. Both of these approaches are used because both approaches are often used in decision support systems, so it is expected to be used to determine strategies that can be used to improve the character of young people in maintaining relations between Chinese-Indonesian culture.